Adversity Quetient, Self Efficacy dan Kesiapan kerja Siswa Kelas XII Program Keahlian Multimedia SMKN 1 Kabupaten Jombang - Wibowo, Ari; ., Suroso (Persona:Jurnal Psikologi Indonesia, 2016)
This study aims to determine (1) The relationship adversity quotient with work readiness, (2) The relationship of self-efficacy with work readiness, (3) The relationship adversity quotient and self efficacy with work readiness student class XII Multimedia Skills Program of SMK 1 Jombang. The population of this study is all students of class XII Multimedia skills program of SMK Negeri 1 Jombang as many as 316 students. Data collection using a scale. The trials of research instruments conducted to the students of SMKN 2 Jombang as many as 80 students of class XII Multimedia Skills Program. Testing of prerequisite analysis includes normality test and linearity test. The data analysis technique used is the technique of multiple regression analysis. The results of this study are (1) Adversity Quetientand Self effiacy havepositive and significant impact to the Work Readiness of students class XII Multimedia Skills Program SMKN 1 Jombang. indicated by the test results of the regression analysis to get the value of the regression F = 13.049, p = 0.000 (p <0.01), (2) Adversity Quetient have positive and significant impact to the work readiness of students class XII of SMKN 1 Jombang.based on the results of the regression partial analysis found Regression t values between variables adversity quetient with work readiness = 4.266 and r partial = 0.437 and p = 0, 000 (p <0.01), (3) Self Efficacy has not positive and significant impact to the work readiness of students class XII of SMKN 1 Jombang indicated by the value of r partial correlation between self-efficacy with work readiness = 0.010, and the value of t regression = 089 and, with p = 0, 930 (p> 0.01).Keywords : Adversity Quotient, Self Efficacy, Job Readiness